Influencia de cambio de uso de suelo en la tasa de deforestación de la cuenca del río Chone, en los años 2008 y 2015 - Falconí Calderón, Luis Adrían (2017)
The objective of this research was to determine the influence of land use change on the deforestation rate in the Chone river basin in 2008 and 2015. Thematic maps were validated for the 2008 and 2015 classifications respectively, were used different cartographic tools and processes such as photo interpretation, the treatment and analysis of Landsat satellite, through supervised classification. Distinguishing the following uses of agricultural land (banana, short cycle crops, long cycle crops and grass), forests, shrimp, water bodies, livestock, bare or unused soil and populated area. The results show that the predominant activity is the agricultural-livestock that in 2008 was 27.86%; with short cycle, long and grass crops. In 2015, the agricultural-livestock activity has reduced to 46.65% the crops of short, long cycle and grass. In these periods, a deforestation rate of 0.08% per year has been recorded for areas with natural cover, specifically for forests, where the transition to afforestation and reforestation with commercial timber species has been demonstrated in 19.66%. It is concluded that land use in the Chone river basin has changed during these years as a result of the increase of secondary forests, expansion of the livestock frontier; Influencing the use of land and the use of natural resources.